Dying to Be Noticed: Epigenetic Regulation of Immunogenic Cell Death for Cancer Immunotherapy - Cruickshank, Brianne; Giacomantonio, Michael; Marcato, Paola; McFarland, Sherri; Pol, Jonathan; Gujar, Shashi (Frontiers in Immunology, 2018)
Immunogenic cell death (ICD) activates both innate and adaptive arms of the immune system during apoptotic cancer cell death. With respect to cancer immunotherapy, the process of ICD elicits enhanced adjuvanticity and antigenicity from dying cancer cells, and consequently, promotes the development of clinically desired anti-tumor immunity. ICD requires the induction of various “hallmarks” of immunomodulation, including, surface translocation of calreticulin, production of type I interferons and release of HMGB1 and ATP, which through their compatible actions induce an immune response against cancer cells. Interestingly, the recent reports investigating the use of epigenetic modifying drugs as anticancer therapeutics have identified several connections to ICD hallmarks. Epigenetic modifiers, such as decitabine have a direct effect on cell viability, and appear to fundamentally change the immunogenic properties of cancer cells by actively subverting tumor microenvironment-associated immuno-evasion, and aiding in the development of an anti-tumor immune response. In this review, we critically discuss the current evidence that identifies direct links between epigenetic modifications and ICD hallmarks, and put forward an otherwise poorly understood potential of epigenetic drugs as ICD-inducers. We further discuss potential therapeutic innovations that aim to induce ICD during epigenetic drug therapy, generating highly efficacious cancer immunotherapies.